PENGGUNAAN MODEL PEMBELAJARAN LEARNING CYCLE 7E UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA POKOK BAHASAN STRUKTUR ATOM DAN SISTEM PERIODIK UNSUR DI KELAS X SMAN 11 PEKANBARU - Zuriatni, Yulisya; Copriady, Jimmi; ', Abdullah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The research about implementation of learning model Learning Cycle 7E has been done with purpose to improve learning result of students on the atomic structure and elements periodic system subject at the class X SMAN 11 Pekanbaru. Learning model Learning Cycle 7E is cycle model that involve student actively through the 7 phase in learning process that is elicit, engage, explore, explain, elaborate, evaluate and extend. This research plan is experiment research by using One Group pretest-posttest Design. The sample consisted of 30 students who are members of the experimental class is class X MIA 5. The technic of data analyze used is t-test paired sample. Tabulation of data result obtained arithmetic-t bigger than table-t that is 46,26 bigger than 2,756; it’s mean there is a significant differences of the student’s learning result with the use of learning model Learning Cycle 7E on the atomic structure and elements periodic system subject at the class X SMAN 11 Pekanbaru.Key Words: Learning Model Learning Cycle 7E, Learning Result, Atomic Structure andElements Periodic System Subject.